(untitled) (INTERNATIONAL SEMINAR, 2023)
Writing is the way and the process of exploring ideas on paper to transfer thoughts into sentences and give them structure and coherent organization. Many students were not interested in and were afraid of writing because they could not understand the way to write. This study aims to know the achievement difference in writing narrative text between the students in writing process design class and those who are in direct method design class. This study uses quantitative research with quasi-experimental research applying a non-randomized pretest-posttest control group design. The research used interviews and some tests for the students. The results show that the student writer undertakes a four-step writing process: Planning the process, Drafting/outlining, Editing the paragraph, and Final writing using process writing give different influences on the student’s achievement of narrative text and the score resulting from this research is valid. The study significantly contributes to the body of knowledge on writing and helps writing teachers and learners of writing using the writing process.